Biogasoline: An out-of-the-box solution to the food-for-fuel and land-use competitions. (1st January 2015) - Hassan, S.N.; Sani, Y.M.; Abdul Aziz, A.R.; Sulaiman, N.M.N.; Daud, W.M.A.W.
Highlights: Reviewed prospects of biogasoline production as alternative to ethanol and biodiesel. Biogasoline promises to be cheaper and more environmental friendly. Inedible feedstocks would ensure higher net energy gain. Inedible feedstocks will resolve food-for-fuel conflicts and land-use competitions. Advances required for producing bioenergy crop and renewable energy sources. Abstract: Societal developments are hinged on the energy supplied by fossil fuels. However, the supply of these fuels is finite in the foreseeable future. This is aside the associated environmental degradation and economic sustainability of these fuels. These negative consequences and challenges spurred the search for sustainable energy sources such as biofuels. However, affordable feedstocks and efficient synthesis for renewable fuels remain indispensable and yet challenging line of research. Therefore, breakthroughs in plant biotechnology and mass production are essential prerequisites for ensuring the sustainability of biofuels as alternatives to petroleum-based energy. Conversely, public outcry concerning the food-for-fuel conflicts and land-use change hinder the popularity of such biofuel energy sources. Therefore, this paper reviewed the prospects of biogasoline production as sustainable alternative to ethanol and a compliment to biodiesel. Apart from reduction in greenhouse gas emissions, biogasoline promises to be cheaper and more environmental friendly. Further, inedible feedstocks such as microalgae and rubber seed oil would ensure higher net energy gain. Consequently, these will help resolve the food-for-fuel conflicts and land-use competitions. However, achieving the biofuel central policy depends on advances in processing the renewable energy sources.